Strategies for Word Order Variation Repair between English and Tshivenda at a Rural University - Nephawe, Farisani Thomas (International Journal of Language and Literary Studies, 2022)
Competence in rules for arranging appropriate word order in sentences avoids ambiguity and misinterpretation in communication. Nevertheless, non-native English speakers experience difficulties in word order due to variations between English and Tshivenda. This paper examined strategies for word order variation repair between the two languages. A qualitative research approach was adopted to obtain an in-depth understanding of the use of word order in written essays. An action research method was utilised as it is a critical classroom-based inquiry for identifying and improving the teaching and learning of a particular grammatical aspect. Data were collected from 15 purposefully selected Module 1141 English Communication Skills students at the University of Venda, South Africa. A pilot study was conducted on the use of word order by 10 students who were not part of the study group but shared similar characteristics with them. After utilising discourse critical analysis, it was revealed that learners experienced difficulties regarding declarative, interrogative and negative sentences. However, after employing scaffolding strategies, the students' performance was preternatural because the lowest challenge was misformation, with only 8%, while misordering had 11%. Therefore, scaffolding strategies are recommended in teaching and learning English word order.